Association of depressive symptoms and suicidal ideation among university students in China: A systematic review and meta-analysis. Issue 13 (March 2017) - Wang, Yu-Hang; Shi, Zhou-Ting; Luo, Qian-Ying
Abstract : Abstract: The aim of this study was to investigate whether depressive symptoms are associated with suicidal ideation among university students in China. Five Chinese and English electronic databases (EBSCO, PubMed, Chinese Web of Knowledge, Wanfang, and Weipu) were searched to identify relevant studies. Cross-sectional studies published from 2000 to 2016 reporting about the association between depressive symptoms and suicidal ideation among university students in China were used for meta-analysis to approximate the overall association between depression and suicidal ideation among university students in mainland China. StatsDirect 3 was used for meta-analysis of included literatures. Of 513 initially identified references, 44 studies were selected, including 88, 431 participants with depressive symptoms. The combined odd ratio of the relationship was 2.174 (95% confidence interval: 2.027–2.333; P  < 0.0001). There exists a moderate association between depressive symptoms and suicidal ideation among university students in China, and depressive symptoms contribute to the development of suicidal ideation. In particular, university students from western regions of China, from nonmedical background, should be provided more psychological and clinical assistance.